Distribution, bioavailability, and ecological risk assessment of potentially toxic heavy metals in El-Burullus Lake sediments, Egypt. (June 2023) - Aly-Eldeen, Mohamed A.; Shreadah, Mohamed A.; Abdel Ghani, Safaa A.
Abstract: El-Burullus Lake is the second largest coastal lagoon in Egypt in addition to its connection to the Mediterranean Sea. In this study, geochemical fractionations of heavy metals (Fe, Pb, Cd, Cu, Cr and Zn) were investigated after the great efforts made to rehabilitate and restore the lake by the Egyptian Government. The results indicated that F4 (residual fraction) was the dominant fraction for all studied metals followed by F3 (oxidizable fraction). That means the majority of studied metals source in the lake is lithogenic. Contamination by each individual heavy metal or multi elements was low according to individual contamination factor (ICF) and global contamination factor (GCF). Risk assessment code (RAC) classification showed that Cd and Cu exhibited low risk, Zn was of moderate risk, whereas, other metals are safe. The toxicity calculated by toxic risk index (TRI) indicating that no toxic risk was expected in the Lake. Highlights: Chemical forms of heavy metals (Fe, Pb, Cd, Cu, Cr and Zn) were measured by applying four-step sequential leaching technique Indices revealed that the lake itself did not pose ecological risk compared to drains that may pose a moderate ecological risk. Calculated toxic risk index (TRI) indicated no toxic risk was expected in the Lake Residual fraction (F4) was the dominant fraction for all studied metals.